Improving Students' Cognitive Understanding of Natural Selection Topics Through PhET Simulations - Iin Murtini; Lilik Mawartiningsih; Imas Cintamulya (Universitas Lambung Mangkurat, 2024)
Natural selection is one of the topics of evolution material that is considered difficult for students, so it is necessary to have a practicum to help in understanding this material. Limited laboratory equipment in schools is an obstacle to learning evolution, so learning media are needed to support evolution learning. One of the learning media that can be applied is PhET simulation. PhET simulation supports evolution learning because it provides simulations in the form of processes of how living things experience natural selection mechanisms. This service program aims to describe students' cognitive understanding of the topic of natural selection with the help of the PhET simulation application. This activity is expected to be used as reference material for teachers who conduct practicums with the help of the PhET simulation application. The subjects who participated in this service activity were 30 students in class XII MIPA. The service activities were carried out on June 16–23, 2023, at SMAN 4 Tuban. The service activities carried out include training, discussion, and guidance. Based on the results of the program, it can be seen that the trainees were very enthusiastic about participating in the PhET simulation activities, the use of PhET simulation was easy to apply, and the trainees were easier to understand the material with the help of this application (87% of the time).